EDUCATION OF RELIGIOUS VALUES IN BUILDING HEALTHY PERSONALITY (Analytical Descriptive Study in Madrasah Aliyah Darul Arqam Garut) - Dewi Sadiah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
Educational value as a teaching or counseling leads students to realize the values of truth, goodness, and beauty, through the process of the correct value judgments and habituation to act consistently. This study aims at identifying goals and assessment of religious values education in building healthy characters, and adopts an analytical descriptive method and qualitative approach. People with healthy personalities are those who are judged to be well adjusted. They are so judged because they are able to function efficiently in the word of people. They experience a kind of “inner harmony” in the sense that they are at peace with other as well as with themselves. The teacher expected goals is in line with the vision and mission of Darul Arqam Madrasah Aliyah equipped with extra-curricular activities and school discipline. Someone with a healthy personality can give happiness to her needs through behaviors (adjusted) with the environmental norms and needs of his conscience, thus forming the character of the students become independent, accomplished, happy, sholeh, honest, faithful and pious to Allah SWT.